2018
DOI: 10.1021/jacs.8b09685
|View full text |Cite|
|
Sign up to set email alerts
|

Total Synthesis of (−)-Mitrephorone A

Abstract: The first synthesis of (−)-mitrephorone A is disclosed along with discussion and study of synthetic strategies. The natural product includes a highly congested hexacyclic ent-trachylobane diterpenoid framework featuring a rare, embedded oxetane. The synthetic analysis presented dissects a number of approaches for the synthesis of the central oxetane, including carbonyl-olefin photocycloadditions, Prins-type cyclizations, and oxidative ring closures. In the successful route, three [4 + 2] cycloadditions enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 81 publications
1
36
0
Order By: Relevance
“…Richter et al [83] reported the first and enantioselective synthesis of (−)-mitrephorone A in 2018 by using a novel late-stage oxidative cyclisation (Scheme 7). Synthesis commenced with methacrolein 28 and gave 29 in steps.…”
Section: Oxetanesmentioning
confidence: 99%
“…Richter et al [83] reported the first and enantioselective synthesis of (−)-mitrephorone A in 2018 by using a novel late-stage oxidative cyclisation (Scheme 7). Synthesis commenced with methacrolein 28 and gave 29 in steps.…”
Section: Oxetanesmentioning
confidence: 99%
“…The direct α-acetoxylation of ketones provides an efficient and synthetically practical method for α-oxygen functionalization of carbonyl compounds, which exhibits various applications as synthetic key precursors and versatile synthons in organic synthesis (Mizukami et al, 1978 ; Hecker and Werner, 1993 ; Varma et al, 1998 ; Kaila et al, 2007 ; Edwards et al, 2008 ; Richter et al, 2018 ; Huang et al, 2019 ). Therefore, considerable efforts have been made in the development of synthetic protocols for α-acetoxylation of ketones ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the first and enantioselective total synthesis of (−)-mitrephorone A ( 1 ), which lacked diastereocontrol. 3 Herein, we report a new route for a highly enantio- and diastereoselective synthesis of 1 . Our retrosynthetic analysis involved disconnection of (−)-mitrephorone A ( 1 ) to 2 ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%